Information sharing challenges in end-of-life care: a qualitative study of patient, family and professional perspectives on the potential of an Electronic Palliative Care Co-ordination System - Mark Lee; Katie Brittain; Catherine Exley; Holly Standing; Monique Lhussier; Angela Bate; Sonia Michelle Dalkin; Rebecca Patterson (BMJ Open)
Objectives To explore current challenges in interdisciplinary management of end-of-life care in the community and the potential of an Electronic Palliative Care Co-ordination System (EPaCCS) to facilitate the delivery of care that meets patient preferences.Design Qualitative study using interviews and focus groups.Setting Health and Social Care Services in the North of England.Participants 71 participants, 62 health and social care professionals, 9 patients and family members.Results Four key themes were identified: information sharing challenges; information sharing systems; perceived benefits of an EPaCCS and barriers to use and requirements for an EPaCCS. Challenges in sharing information were a source of frustration for health and social care professionals as well as patients, and were suggested to result in inappropriate hospital admissions. Current systems were perceived by participants to not work well—paper advance care planning (ACP) documentation was often unavailable or inaccessible, meaning it could not be used to inform decision-making at the point of care. Participants acknowledged the benefits of an EPaCCS to facilitate information sharing; however, they also raised concerns about confidentiality, and availability of the increased time and resources required to access and maintain such a system.Conclusions EPaCCS offer a potential solution to information sharing challenges in end-of-life care. However, our findings suggest that there are issues in the initiation and documentation of end-of-life discussions that must be addressed through investment in training in order to ensure that there is sufficient information regarding ACP to populate the system. There is a need for further qualitative research evaluating use of an EPaCCS, which explores benefits and challenges, uptake and reasons for disparities in use to better understand the potential utility and implications of such systems.